Encapsulation of rat bone marrow stromal cells using a poly‐ion complex gel of chitosan and succinylated poly(Pro–Hyp–Gly). (28th January 2015) - Kusumastuti, Yuni; Shibasaki, Yoshiaki; Hirohara, Shiho; Kobayashi, Mime; Terada, Kayo; Ando, Tsuyoshi; Tanihara, Masao
Abstract: Encapsulation of stem cells into a three‐dimensional (3D) scaffold is necessary to achieve tissue regeneration. Prefabricated 3D scaffolds, such as fibres or porous sponges, have limitations regarding homogeneous cell distribution. Hydrogels that can encapsulate cells such as animal‐derived collagen gels need adjustment of the pH and/or temperature upon cell mixing. In this report, we fabricated a poly‐ion complex (PIC) hydrogel of chitosan and succinylated poly(Pro–Hyp–Gly) and assessed its effect on cell viability after encapsulation of rat bone marrow stromal cells. PIC hydrogels were obtained successfully with a concentration of each precursor as low as 3.0–3.8 mg/ml. The maximum gelation and swelling ratios were achieved with an equal molar ratio (1:1) of anionic and cationic groups. Using chitosan acetate as a cationic precursor produced a PIC hydrogel with both a significantly greater gelation ratio and a better swelling ratio than chitosan chloride. Ammonium succinylated poly(Pro–Hyp–Gly) as an anionic precursor gave similar gelation and swelling ratios to those of sodium succinylated poly(Pro–Hyp–Gly). Cell encapsulation was also achieved successfully by mixing rat bone marrow stromal cells with the PIC hydrogel simultaneously during its formation. The PIC hydrogel was maintained in the culture medium for 7 days at 37°C and the encapsulated cells survived and proliferated in it. Although it is necessary to improve its functionality, this PIC hydrogel has the potential to act as a 3D scaffold for cell encapsulation and tissue regeneration. Copyright © 2015 John Wiley & Sons, Ltd.